Screening potential antileukemia ingredients from sweet potato: integration of metabolomics analysis, network pharmacology, and experimental validation - Xu, Lianling; Zeng, Kaixuan; Duan, Zuoyue; Liu, Jing; Zeng, Yan; Zhang, Miao; Yang, You; Guo, Qulian; Jin, Yanling; Liu, Wenjun; Guo, Ling (Frontiers in Nutrition, 2025)
BackgroundActive dietary flavonoids are a promising resource for novel drug discovery. Sweet potato, a widely cultivated functional crop, is abundant in flavonoids. However, the active ingredients associated with acute myeloid leukemia (AML) treatment and their underlying mechanisms have not been reported to date.ObjectiveThis study aims to identify novel drugs against AML from sweet potato by integrating metabolomics analysis, network pharmacology, and experimental validation.MethodsFirstly, ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) was employed to analyze the major constituents in sweet potato. Then, nine active ingredients were selected for validation of their anti-leukemia effects. Subsequently, three of them underwent network pharmacology analyses and in vitro experimental verification. Finally, the anti-leukemia effect of cynaroside was further confirmed through in vivo experimental validation.ResultsFirstly, the flavonoid content of stem, leaves, flesh, and peel from 13 sweet potato cultivars was examined. The leaves of Nanshu 017 exhibited the highest flavonoid content of 2.27% dry weight (DW). Then, an extract derived from these leaves was employed for in vitro experiments, demonstrating significant inhibition of AML cell growth. Subsequently, based on the results of metabolomics analysis and network pharmacology, cynaroside, nepitrin, and yuanhuanin were identified as potential antileukemia agents present in sweet potato for the first time; while CASP3, KDR, EGFR, and SRC were recognized as pivotal targets of these three monomers against AML. Finally, the antileukemia effects of cynaroside, nepitrin, and yuanhuanin were confirmed through in vitro and in vivo experimental validation.ConclusionIn summary, sweet potato leaves extract possesses an antileukemic effect while cynaroside, nepitrin, and yuanhuanin demonstrate potential as treatments for AML.